Increased sucrose consumption in mice gene-targeted for Vmat2 selectively in NeuroD6-positive neurons of the ventral tegmental area - Bimpisidis, Zisis; Serra, Gian Pietro; König, Niclas; Wallén-Mackenzie, Åsa (Frontiers in Molecular Neuroscience, 2023)
Ventral tegmental area (VTA) dopamine (DA) neurons are implicated in reward processing, motivation, reward prediction error, and in substance use disorder. Recent studies have identified distinct neuronal subpopulations within the VTA that can be clustered based on their molecular identity, neurotransmitter profile, physiology, projections and behavioral role. One such subpopulation is characterized by expression of the NeuroD6 gene, and projects primarily to the nucleus accumbens medial shell. We recently showed that optogenetic stimulation of these neurons induces real-time place preference while their targeted deletion of the Vmat2 gene caused altered response to rewarding substances, including ethanol and psychostimulants. Based on these recent findings, we wanted to further investigate the involvement of the NeuroD6-positive VTA subpopulation in reward processing. Using the same NeuroD6Cre+/wt;Vmat2flox/flox mice as in our prior study, we now addressed the ability of the mice to process sucrose reward. In order to assess appetitive behavior and motivation to obtain sucrose reward, we tested conditional knockout (cKO) and control littermate mice in an operant sucrose self-administration paradigm. We observed that cKO mice demonstrate higher response rates to the operant task and consume more sucrose rewards than control mice. However, their motivation to obtain sucrose is identical to that of control mice. Our results highlight previous observations that appetitive behavior and motivation to obtain rewards can be served by distinct neuronal circuits, and demonstrate that the NeuroD6 VTA subpopulation is involved in mediating the former, but not the latter. Together with previous studies on the NeuroD6 subpopulation, our findings pinpoint the importance of unraveling the molecular and functional role of VTA subpopulations in order to better understand normal behavior and psychiatric disease.